2011
DOI: 10.1007/s00405-011-1748-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between history, laryngoscopy and esophagogastroduodenoscopy for diagnosis of laryngopharyngeal reflux in patients with typical GERD

Abstract: The techniques used in the diagnosis of gastroesophageal reflux disease (GERD) have insufficient specificity and sensitivity in diagnosing laryngopharyngeal reflux (LPR). The purpose of this study was to evaluate the role of esophagogastroduodenoscopy (EGD) and laryngological examination in the diagnosis of LPR. A total of 684 diagnosed GERD and suspected LPR patients were prospectively scored by the reflux finding score (RFS) which was suggested by Koufman. A total of 484 patients with GERD who had RFS ≥ 7 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
2
25
1
Order By: Relevance
“…These results stand in contrast to the study by Jin et al, which showed a significant positive correlation between Jitt and RSI [20]. Other previous studies did not report a correlation between signs and symptoms in LPR patients [42]. However, we found significant correlations between the grade of dysphonia, breathiness, asthenia, instability and the values of Jitt, RAP, Shim, and APQ.…”
Section: Discussioncontrasting
confidence: 99%
“…These results stand in contrast to the study by Jin et al, which showed a significant positive correlation between Jitt and RSI [20]. Other previous studies did not report a correlation between signs and symptoms in LPR patients [42]. However, we found significant correlations between the grade of dysphonia, breathiness, asthenia, instability and the values of Jitt, RAP, Shim, and APQ.…”
Section: Discussioncontrasting
confidence: 99%
“…GERD affects approximately 20% to 40% of the U.S. population, and a significant proportion of these patients (up to 70%) also have LPR . The pathophysiology of GERD and LPR is multifactorial, including esophageal sphincter dysfunction, exposure time of reflux, and tissue sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the prevalence of GERD is 68% in patients with hiatal hernia[24,25]. Recent studies have shown that LPR is found in 70% of patients with GERD, 53% patients with GERD and LPR have hiatal hernia, and approximately 50% of patients with GERD and hernia have common symptoms of LPR[4,26]. In our study, we found that 67.7%-74.2% of patients with LPR and type I hiatal hernia had typical GERD symptoms, similar to a pervious study[26].…”
Section: Discussionmentioning
confidence: 99%
“…The reflux finding score, which is based on laryngoscopic findings, also has poor reliability in detecting LPR[8,9]. Recent evidence has suggested no relationship between clinical findings of LPR, laryngoscopy, and the reflux finding score[26]. Monitoring of pH can directly detect increased esophageal or laryngopharyngeal acid exposure by a pH probe, and is thus regarded as the best evidence for diagnosis of LPR.…”
Section: Discussionmentioning
confidence: 99%